The Genomic Characteristics of ALK Fusion Positive Tumors in Chinese NSCLC Patients - Liu, Shaokun; Huang, Tanxiao; Liu, Ming; He, Wenlong; Zhao, YingShen; Yang, Lizhen; Long, Yingjiao; Zong, Dandan; Zeng, Huihui; Liu, Yuanyuan; Liao, Wenting; Duan, Jingxian; et al. (Frontiers in Oncology, 2020)
Anaplastic lymphoma kinase (ALK) fusion events account for approximately 3-7% genetic alterations in non-small cell lung cancer (NSCLC) patients. In this study, we revealed the comprehensive genomic landscape of 44 ALK positive NSCLC patients using a 605-gene panel, and identified ALK fusion partners. The most common partner is EML4, forming the variant 1 (v1, E13:A20, 18/44), variant 2 (v2, E20:A20, 5/44), and variant 3 (v3, E6:A20, 13/44). Except for the novel partner gene EML4, we detected a new ALK fusion partner HMBOX1. At the mutation level, TP53 is the most frequently mutated gene (24%), followed by ALK (12%) and STED2 (12%). The median tumor mutation burden (TMB) of these samples is 2.29 mutations/Mb, with a range between 0.76-16.79 mutations/Mb. We further elaborately portrayed the TP53 mutation sites on protein structure in lollipop plots. We also presented their mutational signature and copy number alterations (CNAs). The CNA events were found in 13 (13/44) patients, and the most commonly amplified genes were MDM2 (n = 4/13) and TERT (n = 4/13). This result can provide genomic information for personalized clinical management of patients with ALK fusion in the era of precision medicine.